MODEL KERUANGAN UNTUK IDENTIFIKASI KAWASAN RAWAN LONGSOR - Imam Buchori; Joko Susilo (TATALOKA, 2012)
This study aims to develop a spatial model based on Geographic Information System (GIS) that can be used to identify landslide prone areas. The model uses map overlay and tabular weighted methods involving seven variables, i.e. slope, geological condition, rainfall, soil water, water infiltration, earthquake zone, and land cover. Output of the model are classified into three categories: very vulnerable, somewhat vulnerable and safe. To ensure that the model can work well, it is applied in Semarang City due to the consideration that it has various topographical conditions, i.e. flat on the North side and hilly on the South side. Besides, the high population density has been increasing population activities, which in turn increses environmental vulnerability. To validate the model, its output is compared with the real situation on the field using some sample points.The result has shown that the model can work well, with a validity of approximately 92.5%. The output map shows that the very prone landslide area of Semarang City is about 306.82 hectare or 1% of the city’s area. Furthermore, the model is supposed to be aplicable in other areas having the same characteristics as Semarang City.